Isolation and characterization of new thermophilic aminoacylase from Geobacillus sp. Strain Szn - Suzana Adenan (Tanjong Malim, 2018)
Isolation and characterization of new thermophilic aminoacylase from Geobacillus sp. Strain Szn by Suzana Adenan